Attenuated infection by a Pteropine orthoreovirus isolated from an Egyptian fruit bat in Zambia. - Hayato Harima; Michihito Sasaki; Yasuko Orba; Kosuke Okuya; Yongjin Qiu; Christida E Wastika; Katendi Changula; Masahiro Kajihara; Edgar Simulundu; Tomoyuki Yamaguchi; Yoshiki Eto; Akina Mori-Kajihara; et al. (Public Library of Science (PLoS), 2021)
Background Pteropine orthoreovirus (PRV) is an emerging bat-borne zoonotic virus that causes severe respiratory illness in humans. Although PRVs have been identified in fruit bats and humans in Australia and Asia, little is known about the prevalence of PRV infection in Africa. Therefore, this study performed an PRV surveillance in fruit bats in Zambia. Methods Egyptian fruit bats (Rousettus aegyptiacus, n = 47) and straw-colored fruit bats (Eidolon helvum, n = 33) captured in Zambia in 2017-2018 were screened for PRV infection using RT-PCR and serum neutralization tests. The complete genome sequence of an isolated PRV strain was determined by next generation sequencing and subjected to BLAST and phylogenetic analyses. Replication capacity and pathogenicity of the strain were investigated using Vero E6 cell cultures and BALB/c mice, respectively. Results An PRV strain, tentatively named Nachunsulwe-57, was isolated from one Egyptian fruit bat. Serological assays demonstrated that 98% of sera (69/70) collected from Egyptian fruit bats (n = 37) and straw-colored fruit bats (n = 33) had neutralizing antibodies against PRV. Genetic analyses revealed that all 10 genome segments of Nachunsulwe-57 were closely related to a bat-derived Kasama strain found in Uganda. Nachunsulwe-57 showed less efficiency in viral growth and lower pathogenicity in mice than another PRV strain, Miyazaki-Bali/2007, isolated from a patient. Conclusions A high proportion of Egyptian fruit bats and straw-colored fruit bats were found to be seropositive to PRV in Zambia. Importantly, a new PRV strain (Nachunsulwe-57) was isolated from an Egyptian fruit bat in Zambia, which had relatively weak pathogenicity in mice. Taken together, our findings provide new epidemiological insights about PRV infection in bats and indicate the first isolation of an PRV strain that may have low pathogenicity to humans.